Prevention Behavior Factor Relationship On Malaria Events In Pregnant Women In Sibolga City In 2020 - Friska A. Sihombing; Syarul Khairiaty; Krisniat (Science Midwifery, 2020)
Malaria infection in pregnancy is detrimental to the mother and fetus because it can increase maternal and fetal morbidity and mortality. Data on maternal mortality in the city of Sibolga in 2020, shows that maternal mortality based on malaria is in third place. The purpose of the study was to analyze the effect of preventive behavior factors (use of mosquito nets, installation of wire netting, use of mosquito repellent and the habit of being outside at night) on the incidence of malaria in pregnant women in the city of Sibolga. The study was conducted using a case control research design. The sampling technique used was Multi Stage Sampling with a sample size of 90 people. Data analysis used bivariable analysis. The results showed that pregnant women who did not use mosquito nets and or had a habit of being outside the house at night had a greater risk of being infected with malaria in Sibolga City p = 0.000 (OR 8.389, 95% CI: 3.152-22.292) and p : 0.010 (OR : 3.143, 95% CI : 1.300-7.599). Thus, there is a need for equitable distribution, monitoring of the use and maintenance of insecticide-treated mosquito nets and the need to identify local potentials that can be used as mosquito repellent media and can also utilize mosquito repellent plants, such as zodia, basil, geranium, suren, lavender, lemongrass and neem.